1967
DOI: 10.1113/jphysiol.1967.sp008334
|View full text |Cite
|
Sign up to set email alerts
|

5‐Hydroxytryptamine participation in the vagal inhibitory innervation of the stomach

Abstract: 1. Intraluminal pressure was recorded from the isolated guinea-pig and mouse stomach with the vagus and sympathetic nerves attached.2. The response to vagal stimulation, which consists of an excitatory and an inhibitory component, resembled the response to 5-hydroxytryptamine (5-HT), which has no direct action on the muscle but acts on intrinsic excitatory and inhibitory ganglia.3. In the presence of hyoscine, the effect of vagal stimulation, of nicotinic compounds and of 5-HT were all purely relaxant. Competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
1

Year Published

1972
1972
2004
2004

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(81 citation statements)
references
References 39 publications
5
75
1
Order By: Relevance
“…In the isolated intact stomach of the guinea-pig, 5-HT caused either a reduction in intraluminal pressure or a diphasic response, namely, an increase followed by a decrease (Gershon, 1967;Bulbring & Gershon, 1967). Since all responses to 5-HT in concentrations of up to 1 ug/ml were abolished by tetrodotoxin, it was concluded 108 T. Yamaguchi that, in the guinea-pig stomach, 5-HT acts indirectly through the nervous components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the isolated intact stomach of the guinea-pig, 5-HT caused either a reduction in intraluminal pressure or a diphasic response, namely, an increase followed by a decrease (Gershon, 1967;Bulbring & Gershon, 1967). Since all responses to 5-HT in concentrations of up to 1 ug/ml were abolished by tetrodotoxin, it was concluded 108 T. Yamaguchi that, in the guinea-pig stomach, 5-HT acts indirectly through the nervous components.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the guinea-pig stomach may contain mainly M receptors, because the effects of 5-hydroxytryptamine (5-HT) (01-1 yg/ml) on intraluminal pressure are blocked by tetrodotoxin (Gershon, 1967;Bulbring & Gershon, 1967). In the presence of tetrodotoxin, only a high concentration of 5-HT (10-100 yg/ml) produces a slight contraction, followed by a slight relaxation (Paton & Vane, 1963;Gershon, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, enteric serotonergic neurons specifically and avidly take up 5-HT, providing an adequate inactivating mechanism for the amine as a transmitter (Gershon and Altman, 1971;Robinson and Gershon, 1971;Gershon et al, 1976;Gershon and Jonakait, 1979). On a gross level, 5-HT also mimics many of the authentic neurally mediated responses of the gut (Brownlee and Johnson, 1963;Bulbring and Gershon, 1967;Furness and Costa, 1973;Costa and Furness, 1979a;Jule, 1980); however, considerable controversy has arisen over whether these gross effects can be traced to physiological actions of 5-HT (see Costa and Furness, 1979b;Gershon, 1982) and over whether nerve-activated, slow excitatory postsynaptic potentials (EPSPs) in enteric neurons are mediated by 5-HT Johnson et al, 1981). Neurons of the myenteric plexus have been categorized as type I or S, type II or AH (Holman et al, 1972;Nishi and North, 1973;Hirst et al, 1974) and, more recently, types III (non-spiking) and IV (delayed spiking; Wood, 1983).…”
mentioning
confidence: 99%
“…It has been suggested that 5-hydroxytryptamine may be involved in the modulation of gastric activity (Bulbring & Gershon, 1967). Therefore an examination of the effects of this compound was included in this study.…”
Section: Discussionmentioning
confidence: 99%